( 2, 4 )
Convert one of the equations to standard form
x + y = 6
(Plug y into the other equation)
x + 2x = 6
3x = 6
x = 2
(Plug x into the y equation)
y = 2(2)
y = 4
There are a few different methods to solve system of equations. For this problem, you can use substitution by solving one of the equations for a variable and then substituting this expression into the other equation to solve for the remaining variable:
x - y = 6, add 'y' to both sides to solve for 'x': x - y + y = 6 + y or x = 6 + y
Using the expression '6 + y' for the value of 'x' in the second equation:
2x + 3y = 12 or 2(6+y) + 3y = 12 or 12 + 2y + 3y = 12 or 12 + 5y = 12
Subtract 12 from both sides: 12 + 5y - 12 = 12 - 12 or 5y = 0 so y = 0
Now that you know the value of 'y', you can solve for 'x':
x = 6 + 0 or x = 6
Put the values of 'x' and 'y' into an ordered pair: (6,0).
x= 6 -y
from both sides of the equation.
/// -78 -78
So, x equals -2 and y equals -8.
Subtituting the value of X in the first equation
Plug y=4 in equation 2.